A lightweight, biodegradable, and recyclable cellulose-based bio-foam with good mechanical strength and water stability. Issue 3 (June 2022) - Liao, Jianming; Luan, Pengcheng; Zhang, Yuxiang; Chen, Li; Huang, Luyao; Mo, Lihuan; Li, Jun; Xiong, Qingang
Abstract: Foam materials have been widely used in a variety of applications. However, plastic foams pose a particularly complex problem to environment because they almost cannot be recycled and degraded in most areas. Here, naturally degradable cellulose-based bio-foams were obtained by combining refined pulp fibers, PAE, and sodium dodecyl sulfate after vigorous mixing, drainage, and drying, where porous structure was formed through internal hydrogen and chemical bonding between cellulose fibers. Mechanical properties of the resulting bio-foams were improved, and the bio-foams exhibit inherent low density, sufficient water stability, excellent natural degradability (93% degradation in 85 days), and good cost-efficiency. Considering low cost of the raw materials, foam designs through our strategy based on cellulosic materials have the potential to be a suitable solution to environmental challenges associated with extensive use of petrochemical-based foams. Graphical Abstract: ga1 Highlights: A cellulosic bio-foam with good mechanical strength and water stability was made. Refined pulp fiber, PAE, and sodium dodecyl sulfate were combined for this bio-foam. Internal crosslinking and chemical bonding between the cellulose fibers are formed. The bio-foam is featured with lightweight, biodegradability, and good recyclability. This bio-foam shows a strong potential to replace petrochemical-based plastic foams.